RANCANGAN THREE-O DENGAN SUMBER DAYA ENERGI KINETIK SEBAGAI INOVASI PENENTU ARAH DAN WAKTU SALAT - Aulliyah, Uunwanah Agustin; Melati, Bunga Chinta; Prasettia, Sukma; Kusumah, Fuji Hernawati (UIN ALAUDDIN MAKASSAR, 2024)
Every Muslim in the world has an obligation to perform prayers, and one of the two valid conditions for prayer is facing the Qibla (the direction of the Ka’bah in Mecca) and praying at the designated times. The challenge arises when someone is in an unfamiliar place where the Qibla direction is unknown. Additionally, prayer times continuously change based on the position of the sun. To address these challenges, the goal of this research is to design a device that can determine the Qibla direction without relying on electricity, signals, internet, or specialized knowledge. This renewable solution aligns with the Sustainable Development Goals (SDGs). The conclusion from this design is successful, resulting in a practical and efficient product for the community, with an average score of 71.4% based on the questionnaire.